2004
DOI: 10.1016/s1368-8375(03)00128-3
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase-1 expression predicts cervical lymph node metastasis of tongue squamous cell carcinomas

Abstract: Heme oxygenase-1 (HO-1) is known as a stress-inducible protein. The presesnt study is designed to investigate the relationship between HO-1 expression levels and clinical features of tongue cancer by using HO-1 responsiveness to stress as a clinical indicator. One hundred and twelve biopsy samples from tongue squamous cell

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
52
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 18 publications
5
52
1
Order By: Relevance
“…Such phenotypes are advantageous for tumour progression and survival. However, a recent paper, denoting the lower HO-1 expression in head and neck carcinomas with LNM, has argued that the increase of HO-1 expression as a cause or a consequence of carcinogenesis (Yanagawa et al, 2004). Preliminary evidences from us indicated that HO-1 promoter polymorphism had no impact on tumour progression, reflecting by metastasis or advanced clinical stage.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Such phenotypes are advantageous for tumour progression and survival. However, a recent paper, denoting the lower HO-1 expression in head and neck carcinomas with LNM, has argued that the increase of HO-1 expression as a cause or a consequence of carcinogenesis (Yanagawa et al, 2004). Preliminary evidences from us indicated that HO-1 promoter polymorphism had no impact on tumour progression, reflecting by metastasis or advanced clinical stage.…”
Section: Discussionmentioning
confidence: 93%
“…Since buccal mucosa is the primary site for the insults of areca, buccal squamous cell carcinoma (BSCC) is the most common subset of OSCC accounting for more than 60% of OSCC in South Asians (Lin et al, 2000;Kao et al, 2002;Lo et al, 2003;Wong et al, 2003). It was found that a subset of OSCC, which occurred on tongue with higher HO-1 expression, contained significantly more differentiated samples and cases without lymph node involvement, which implicated that HO-1 expression could be disadvantageous for OSCC progression (Yanagawa et al, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In cancer, HO-1 has been described as a pro-tumoural molecule due to its antiapoptotic effects on colon cancer and hepatoma on murine models and its proangiogenic effects in human pancreatic cancer (52,53). By contrast, in human tongue cancer, low HO-1 expression has been associated with an increased risk of developing lymph node metastasis (54).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the zinc protoporphyrin, another potent HO-1 inhibitor, has an antineoplastic effect in rats and mice bearing tumors derived from hepatoma and human colon cancer cells (9,76) and also reduces vGPCR-induced tumor growth by 80% (data not shown). Recent evidence shows that HO-1 is overexpressed in pancreatic, gastric, lung, and renal cancer, myeloid leukemia, melanoma, glioma, tongue, thyroid, and hepatocarcinomas (8,12,13,60,61,64,65,70,(75)(76)(77)(78)(79)(80)(81)(82)(83), which are some of the cancer types where RhoA is also overexpressed. Although the link between HO-1 expression and aberrant cell growth is starting to be unraveled, metalloporphyrins that inhibit HO-1 deserve further studies as antitumoral drugs.…”
Section: Discussionmentioning
confidence: 99%